A Call for Career Educators to Recommit to Serving First-Generation and Immigrant College Students: Introduction to Special Issue. (February 2020) - Stebleton, Michael J.; Jehangir, Rashné R.
The purpose of this article is to introduce the special issue on supporting first-generation (FG) and immigrant college students. Just as Parsons and other progressive leaders of the 20th century supported marginalized populations, we echo the call for career development educators to assume the mantle of advocating for equity and social justice causes. All articles in this special issue address these principles focused on supporting FG and/or immigrant college students. An overview and summary of the main articles in the issue are highlighted.